2022
DOI: 10.1063/5.0072994
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated steady-state electrostatic particle-in-cell simulation of Langmuir probes

Abstract: First-principles particle-in-cell (PIC) simulation is a powerful tool for understanding plasma behavior, but this power often comes at great computational expense. Artificially reducing the ion/electron mass ratio is a time-honored practice to reduce simulation costs. Usually, this is a severe approximation. However, for steady-state collisionless, electrostatic (Vlasov–Poisson) systems, the solution with reduced mass ratio can be scaled to the solution for the real mass ratio, with no approximation. This “sca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…46,48) One of the basic assumptions is that plasma components obey the Maxwellian distribution, 49) while a significant population of particles may be trapped near the probe, which is non-ideal. 23) So, with the established sheath model, the present results can be helpful to extend the method of calculating parameters from raw probe data, which may lead to a more precise measurement with electric probes.…”
Section: -5mentioning
confidence: 83%
See 1 more Smart Citation
“…46,48) One of the basic assumptions is that plasma components obey the Maxwellian distribution, 49) while a significant population of particles may be trapped near the probe, which is non-ideal. 23) So, with the established sheath model, the present results can be helpful to extend the method of calculating parameters from raw probe data, which may lead to a more precise measurement with electric probes.…”
Section: -5mentioning
confidence: 83%
“…On the basis of an unmagnetized collisionless plasma, the simulation of a cylindrical Langmuir probe showed that, due to small fluctuations, a significant population of trapped ions appeared around the probe. 23) In the framework of particle-incell simulations applied to the Enceladus plume, Farrell et al demonstrated that there is a trend for low-energy ions to be adsorbed and trapped within the sheath of negatively charged dust grains. 24) Moreover, the presence of trapped particles is widely discussed in theory.…”
Section: Introductionmentioning
confidence: 99%
“…Potential applications for the SLPIC method include its use in the modeling of plasma thrusters (wherein very small electron/ion mass ratios impose especially demanding numerical constraints) and sheath formation (e.g. near a Langmuir probe 12 ). Collisional lowtemperature plasma discharges are also an area of particular interest; recent efforts have demonstrated that SLPIC can be used in conjunction with standard Monte Carlo collision techniques, in the same manner as is done in collisional PIC discharge modeling (PIC-MCC) 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Second, the electron and ion mass disparity makes our explicit solvers very expensive during the transient process (when 𝑛𝑛 � 𝑒𝑒 ≠ 𝑛𝑛 � 𝑖𝑖 ) due to CFL limitations. This challenge can be resolved using an artificially small mass ratio, which does not substantially affect the steady solution [11]. The method is based on the fact that in steady-state collisionless electrostatic plasma, the solution with a reduced mass ratio can be scaled to the one for the actual mass ratio.…”
Section: Kinetic Model Of Spherical Plasmasmentioning
confidence: 99%
“…The method is based on the fact that in steady-state collisionless electrostatic plasma, the solution with a reduced mass ratio can be scaled to the one for the actual mass ratio. It has been successfully used for speed-limited particle-in-cell (SLPIC) simulations [11].…”
Section: Kinetic Model Of Spherical Plasmasmentioning
confidence: 99%